1993
DOI: 10.1111/j.1528-1157.1993.tb02393.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine and Lamotrigine in Healthy Volunteers: Relevance to Early Tolerance and Clinical Trial Dosage

Abstract: This study was conducted to examine the effects of acute doses of lamotrigine (LTG) and carbamazepine (CBZ) in healthy subjects and determine whether the low tendency to impairment with LTG observed in animals applied to humans. Twelve healthy men participated in a placebo-controlled, balanced, double-blind comparison of the drugs on a series of psychomotor, autonomic, sensory, and subjective variables. Variables were analyzed by analysis of variance, and p < 0.05 was considered significant. Adaptive tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 23 publications
2
31
0
2
Order By: Relevance
“…The superiority of lamotrigine over older AEDs has been demonstrated in multiple healthy volunteer studies (A. P. Aldenkamp et al 2002;Cohen et al 1985;Hamilton et al 1993).…”
Section: Lamotrigine (Lamictal)mentioning
confidence: 95%
See 1 more Smart Citation
“…The superiority of lamotrigine over older AEDs has been demonstrated in multiple healthy volunteer studies (A. P. Aldenkamp et al 2002;Cohen et al 1985;Hamilton et al 1993).…”
Section: Lamotrigine (Lamictal)mentioning
confidence: 95%
“…Lamotrigine is associated with fewer CNS adverse effects on measures such as eye movements and body sway than diazepam, carbamazepine, and phenytoin (Cohen et al 1985;Hamilton et al 1993), and is associated with better neuropsychological outcome compared to carbamazepine in more than half of neuropsychological measures employed (e.g., cognitive speed, memory, mood factors, sedation, perception of cognitive performance, and quality of life) in healthy volunteers . The superiority of lamotrigine over older AEDs has been demonstrated in multiple healthy volunteer studies (A. P. Aldenkamp et al 2002;Cohen et al 1985;Hamilton et al 1993).…”
Section: Lamotrigine (Lamictal)mentioning
confidence: 98%
“…While a more recent case report suggested lamotrigine to affect eye movements in children (Das, Harris, Smyth, & Cross, 2003), an earlier study with a larger sample of healthy volunteers found no evidence for this effect (Hamilton et al, 1993) and instead related carbamazepine to alterations in smooth and saccadic eye movements. Importantly, this study found no effects on pupil dynamics and neither did another study for valproate (DeMet & Sokolski, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…Einmaldosen bis 300 mg Lamotrigin hatten bei Gesunden auch in einer anderen Studie keinen Einfluss auf die Reaktionszeit [44]. 63,93], Rhabdomyolyse, Hautausschlag und Ataxie berichtet wurde [93], ferner über einen Fall mit fulminantem Leberversagen unter Lamotrigin [64].…”
Section: Spezielle Organsysteme Haut Und Immunsystemunclassified